Article 371 As an Instrument of Asymmetrical Federalism: Its Philosophical Intent and Contemporary Relevance - Thangzamang Ngaihte (The Bioscan, 2026)
Article 371 and its sub-clauses constitute one of the Constitution’s most consequential, yet insufficiently theorized devices for institutionalizing asymmetrical federalism in India. Although the constitutional scheme is often described as quasi-federal with a pronounced unitary tilt, Article 371 indicates a parallel design logic: the deliberate use of differentiated arrangements to secure integration without erasure in a society marked by deep regional, cultural, and developmental heterogeneity. This article examines Article 371 as a constitutional architecture of accommodation, tracing its historical emergence, mapping the distinct purposes served by clauses 371A to 371J, and analysis the legal form through which autonomy, recognition, and distributive concerns are translated into governance. Drawing on debates in cooperative and polycentric federalism, multicultural citizenship, constitutional patriotism, and constitutional pluralism, it argues that Article 371 is best understood not as episodic political bargaining but as an enduring commitment to protect vulnerable communities, preserve culturally embedded institutions, especially customary law and land regimes in parts of the Northeast and address structural regional inequalities. The article further situates Article 371 in contemporary constitutional politics shaped by post-2019 centralizing impulses, renewed contests over uniformity, resource governance disputes, and persistent demands for autonomy. It concludes that Article 371 remains a stabilizing constitutional mechanism: it operationalize a substantive conception of equality by recognizing that, in a diverse federation, equal citizenship may require differentiated constitutional safeguards. Keywords Article 371, Asymmetrical federalism, Indian Constitution Autonomy, Northeast India, Regionalism, Multiculturalism, Constitutional Design, Customary Law, Political Identity.